Promosi Penjualan, Harga Dan Wom Terhadap Pengambilan Keputusan Pembelian Bubble Wrap PT. Heksagonal Dagang Internasional - Marlindawaty, Marlindawaty; Lestari, Winda (Jurnal GeoEkonomi, 2025)
The growing need for protective plastic packaging that functions as packaging and protects electronics, glassware or products that are at risk of cracking has encouraged retail companies and distributors of bubble wrap products, PT. Heksagonal Dagang International to offer products that suit consumers desires and needs at competitive prices. The purpose of this research is to determine and analyze the extent of sales promotions and price and the role of WOM (Word of Mouth) in influencing consumer purchasing decisions on bubble wrap products produced by PT. Heksagonal Dagang International Balikpapan. This quantitative research uses multiple linear regression analysis techniques. The population in this research were consumers who met the criteria for having purchased bubble wrap measuring 1 meter to 50 meters. Sampling used purposive sampling technique and sample calculation using Green’s formula until a sample of 84 respondents was determined. The partial analysis results show that price and WOM (Word of Mouth) influence consumer purchasing decisions on PT. Heksagonal Dagang International’s bubble wrap products, while sales promotions have no effect. Simultaneously, sales promotion, price and WOM (Word of Mouth) have a significant influence on consumer purchasing decisions on PT. Heksagonal Dagang International’s bubble wrap products.